2015
DOI: 10.1159/000381097
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Activation Does Not Affect Re-Endothelialization but Reduces Intimal Hyperplasia via Direct Effects on Smooth Muscle Cells in a Nondiabetic Model of Arterial Injury

Abstract: Diabetic patients have an increased risk of restenosis and late stent thrombosis after angioplasty, i.e. complications that are related to a defective re-endothelialization. Exendin-4, a stable glucagon-like peptide (GLP)-1 receptor agonist, has been suggested to influence the formation of intimal hyperplasia and to increase endothelial cell proliferation in vitro. Thus, the aim of this study was to investigate the mechanisms by which treatment with exendin-4 could influence re-endothelialization and intimal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
4
16
1
Order By: Relevance
“…Studies in experimental animals have demonstrated that liraglutide accelerates endothelial recovery after injury (41), retards atheroma formation in apolipoprotein E knockout mice (42), exerts anti-inflammatory effects on the vasculature, and inhibits reactive oxygen species formation and platelet aggregation (43). Collectively, these actions of GLP-1 RAs could slow the atherosclerotic process.…”
Section: Potential Mechanisms To Explain CV Benefitmentioning
confidence: 99%
“…Studies in experimental animals have demonstrated that liraglutide accelerates endothelial recovery after injury (41), retards atheroma formation in apolipoprotein E knockout mice (42), exerts anti-inflammatory effects on the vasculature, and inhibits reactive oxygen species formation and platelet aggregation (43). Collectively, these actions of GLP-1 RAs could slow the atherosclerotic process.…”
Section: Potential Mechanisms To Explain CV Benefitmentioning
confidence: 99%
“…The results of the present study demonstrated no increase of cAMP upon increasing the GIP concentration at high glucose levels, but GLP-1 increased the cAMP concentration proportional to its concentration. A previous study indicated that there was a significant decrease in proliferation and an increase in the apoptosis of smooth muscle cells in vitro following treatment with exendin-4, this effect appears to be mediated through cAMP signaling (23). Ge et al (24) demonstrated the protective effect of GLP-1 using microvascular endothelial cells whereas the present study used HUVEC as a macrovascular cell line.…”
Section: Discussionmentioning
confidence: 61%
“…In wild‐type mice, exendin‐4(Ex‐4), a GLP‐1 receptor agonist, reduces neointimal hyperplasia after femoral artery wire injury without affecting the metabolic parameters, including glucose tolerability. Similarly, Ex‐4 showed a protective effect against neointimal hyperplasia with reduced VSMC proliferation in a rat model of restenosis. Furthermore, in vitro studies show supportive data that Ex‐4 suppressed rat VSMC proliferation stimulated by platelet‐derived growth factor.…”
Section: Incretins and Dpp‐4 Inhibitors Suppress Neointimal Hyperplasmentioning
confidence: 91%